Coal Diggers of 1937 exhibition display - Hercules Incorporated (1937)
General view of a Hercules Powder Company puppet theater display entitled "Coal Diggers of 1937" advertising Hercoal permissible explosives. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Incorporated; Chemical industry; Corporations; Trade shows; Explosives; Explosives industry; Advertising; Advertising, Industrial; Trade shows; Puppet theater